GERMINATION AND SEEDLING GROWTH OF SOME SELECTED AGRICULTURAL CROPS UNDER VARIOUS ABIOTIC STRESSES - Pattnaik, Bibhudutta; Chaturvedi, Nilima; Kar, Dattatreya (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The aim of this investigation was to evaluate the germination response of Vigna mungo, Vignaradiata, Zea mays and Brassica nigra to different stress conditions. Methods: The germination responses of four agricultural crops, Brassica nigra, Vigna mungo, Vigna radiata and Zea mays, were studied under control conditions in the laboratory. The treatments included three light levels (red, green and white) and dark period for 24 to 48 hrs, three salinity concentrations (100, 300 and 500 mmol/L NaCl), temperature regimes of supra-optimal (35/28 ºC), optimal (28/18 ºC) and sub-optimal (15/08 ºC) and heavy metals (Cd, Pb and Ni) treatments. Results: Best seed germination of all these species was obtained in distilled water (control). Increase in concentration of salinity progressively inhibits the germination in all the selected plants. Light variedly affected seed germination. Seeds were subjected to white light shows highest germination followed by red light. Darkness has no significant effect on seed germination in all the three plants. The seeds subjected to dark treatment showed better germination as well as lower antioxidant activity than those subjected to various light conditions. Similarly the seeds subjected to supra and sub optimal temperatures shows inhibition were adversely affected with inhibited germination rates. Conclusion: The present investigation reveals that , among the four plants B.nigra showed maximum tolerance against various stress conditions with maximum seed germination.